(untitled) (Research, Society and Development, 2021)
Objective: to verify adherence to antiretroviral treatment and viral suppression, according to demographic, clinical and laboratory variables in patients seen at the HIV/AIDS outpatient clinic of HC-Unicamp in 2016. Method: cross-sectional study on the demographic, epidemiological and clinical profile of patients treated at the Outpatient Clinic of Infectious Diseases at Hospital Dia of the State University of Campinas Hospital de Clínicas to assess adherence to ART and any adverse events recorded in 2016. Results: of the 339 medical records sampled from PLWHA, 278 (82.0%) with regular use of antiretrovirals and 293 (86.4%) with undetectable viral load (<40 copies / mL). The multiple logistic models, age, clinical complications, and side effects of medications are associated with lower adherence to ART. Viral suppression was more significant among men, with older age and shorter diagnosis time, and less frequent in patients with clinical complications and adverse effects of the medication. Conclusion: a greater integration between services can facilitate the rescue of PLWHA without clinical follow-up. The clinical management of complications and adverse drug events are relevant to treatment adherence and viral suppression in patients attending the services.